Shadow netWorkspace: An open source intranet for learning communities - James M Laffey; Dale Musser (The Canadian Network for Innovation in Education (CNIE), 2006)
Shadow netWorkspace (SNS) is a web application system that allows a school or any type of community to establish an intranet with network workspaces for all members and groups. The goal of SNS has been to make it easy for schools and other educational organizations to provide network services in support of implementing a learning community. SNS is open source software using the GNU General Public License (GPL). The software is freely available, and can be downloaded and distributed under the terms of the GPL. SNS is an ongoing project and this instructional development report describes the system, some ways that it is being used, and some key lessons learned from the development and initial deployment of SNS.